Voltammetric Sensing of Caffeine in Food Sample Using Cu‐MOF and Graphene. Issue 4 (9th December 2020) - Venkadesh, A.; Mathiyarasu, J.; Radhakrishnan, S.
Abstract: Cu‐MOF/graphene composite were obtained by solvothermal and electrochemical methods. The interaction and formation of Cu‐MOF/graphene (GE) composite was systematically studied with the support of various characterizations including X‐ray diffraction (XRD), field emission scanning electron microscopy (FE‐SEM) and cyclic voltammogram (CV). The Cu‐MOF/graphene composite coated glassy carbon (GC) electrode exhibited good catalytic performance towards the electro‐oxidation of caffeine in neutral condition. The modified electrode displayed good linear range (5 μM to 450 μM), sensitivity (0.710 μA μM −1 cm −2 ), detection limit (1.38 μM), selectivity, high stability and reproducibility. Finally, the fabricated electrode extended into successful detection of caffeine in tea and coffee samples with good recoveries. Abstract :